Treatment of Localized Infections in Hard-to-Heal Wounds: An Integrative Review (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To identify the knowledge production on the treatment of localized infections in hard-to-heal wounds. Method: An integrative literature review was conducted in the Virtual Health Library, Nursing Database, Scientific Electronic Library Online, Web of Science, Cochrane Library, Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, and PubMed. The selected articles had no time limit. The studies were exported to the Rayyan application and subjected to double-blind evaluation through title and abstract reading, based on inclusion and exclusion criteria. The information was analyzed and synthesized according to the level of evidence. Results: A total of 19 publications were fully analyzed. The evidence obtained on the topic includes wound hygiene, cleaning with 1% acetic acid, identification and treatment of biofilms, the use of dressings, and solutions with antimicrobial action. Conclusion: Localized wound infections have been the subject of various research studies, and the recommended practices refer to topical treatments.